2009
DOI: 10.1002/cmdc.200900362
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Screening against p50 NF‐κB Transcription Factor for the Identification of Inhibitors of the NF‐κB–DNA Interaction and Expression of NF‐κB Upregulated Genes

Abstract: Virtual screening against NF-kappaB p50 using docking simulations was applied by starting from a three-dimensional (3D) database containing more than 4.6 million commercially available structures. This database was filtered by specifying a subset of commercially available compounds sharing a (2E,Z)-3-(2-hydroxyphenyl)-2-propenoate substructure and relevant druglike properties. Docking to p50 NF-kappaB was performed with a test set of six known inhibitors of NF-kappaB-DNA interactions. In agreement with docking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 51 publications
(20 reference statements)
2
22
0
Order By: Relevance
“…Docking simulations to p50 NF-jB were performed with a test set of six known inhibitors of NF-jB/DNA interactions. 18,19 In agreement with docking results, the highest-scored compound (compound 1, see Fig. 1) displayed a high level of inhibitory activity in electrophoretic mobility shift assay (EMSA) experiments (inhibition of NF-jB/DNA interactions) 20,21 and on biological functions dependent on NF-jB activity (inhibition of IL-8 gene expression in cystic fibrosis IB3-1 cells).…”
Section: Introductionsupporting
confidence: 78%
See 4 more Smart Citations
“…Docking simulations to p50 NF-jB were performed with a test set of six known inhibitors of NF-jB/DNA interactions. 18,19 In agreement with docking results, the highest-scored compound (compound 1, see Fig. 1) displayed a high level of inhibitory activity in electrophoretic mobility shift assay (EMSA) experiments (inhibition of NF-jB/DNA interactions) 20,21 and on biological functions dependent on NF-jB activity (inhibition of IL-8 gene expression in cystic fibrosis IB3-1 cells).…”
Section: Introductionsupporting
confidence: 78%
“…1) displayed a high level of inhibitory activity in electrophoretic mobility shift assay (EMSA) experiments (inhibition of NF-jB/DNA interactions) 20,21 and on biological functions dependent on NF-jB activity (inhibition of IL-8 gene expression in cystic fibrosis IB3-1 cells). 15,22 We demonstrated that this in silico screening approach is suitable for the identification of low-molecular-weight compounds that inhibit NF-jB/DNA interactions and NF-jB-dependent functions 19 , confirming a previously published study. 18 This and similar approaches are relevant in medicinal chemistry, as information deduced from the discovery of new lead compounds and their binding mode could result in further lead optimization resulting in more potent NF-jB inhibitors.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations